-4y-9=6y+11

Simple and best practice solution for -4y-9=6y+11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4y-9=6y+11 equation:


Simplifying
-4y + -9 = 6y + 11

Reorder the terms:
-9 + -4y = 6y + 11

Reorder the terms:
-9 + -4y = 11 + 6y

Solving
-9 + -4y = 11 + 6y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-6y' to each side of the equation.
-9 + -4y + -6y = 11 + 6y + -6y

Combine like terms: -4y + -6y = -10y
-9 + -10y = 11 + 6y + -6y

Combine like terms: 6y + -6y = 0
-9 + -10y = 11 + 0
-9 + -10y = 11

Add '9' to each side of the equation.
-9 + 9 + -10y = 11 + 9

Combine like terms: -9 + 9 = 0
0 + -10y = 11 + 9
-10y = 11 + 9

Combine like terms: 11 + 9 = 20
-10y = 20

Divide each side by '-10'.
y = -2

Simplifying
y = -2

See similar equations:

| -2x^2-x=20 | | 11/2X=10 | | X^2+2x+4=3 | | 3(x+5)+2x=5x-15 | | 6x+7x+8=540 | | x^2-(m+1)*x+m=0 | | x^5-7x^3+9x=-x | | 6x+7x+8=360 | | x/187 | | (8,3)x= | | 3(10+x)=3 | | 6x+7x+8=36 | | x-41=-6 | | 12x-3-2x=0 | | 6/7a=16 | | 6x+3-9x=12-15x+12x-9 | | 4a^2+12a-27=0 | | (2/3)x=-9 | | 1/3d(60-t) | | -2(-7+3x)=-22 | | 3(2c-1)-2=2c+3 | | 6(10-3x)=10-8x | | m-20=10 | | 3/14N=3/16 | | (4t+5)(3t+10)=0 | | -8+3x=-4x+55 | | -2(x+1)+x=7-4x | | x-[5+3x-[5x-(6+x)]]=-3 | | 2X=4/15 | | 6x+1=3x+4 | | y+15=-30 | | x-2x+12-3x=-5(x-2)+2 |

Equations solver categories